Progress in systems engineering proceedings of the twenty-third International Conference on Systems Engineering - Selvaraj, Henry; Zydek, Dawid; Chmaj, Grzegorz (Springer International Publishing, 2015)
This collection of proceedings from the International Conference on Systems Engineering, Las Vegas, 2014 is orientated toward systems engineering, including topics like aero-space, power systems, industrial automation and robotics, systems theory, control theory, artificial intelligence, signal processing, decision support, pattern recognition and machine learning, information and communication technologies, image processing, and computer vision as well as its applications. The volume's main focus is on models, algorithms, and software tools that facilitate efficient and convenient utilization.